Need analysis for the development of Kolb and 4C integration learning model-basel lesson plan in Pedagogy Course - Isnawati, Isnawati; Jalinus, Nizwardi (Universitas Negeri Padang, 2020)
This study aims to: 1) Analyze the learning process to obtain information on the needs of lecturers and students as well as expectations in learning pedagogy, 2) analyze the learning styles of students by knowing each learning style of each student, 3) Analysis the learning models such as what was developed that can teach students according to the learning styles of each student. The research method used was a survey method. The data were collected by using questionnaires, interviews and observations. The results of this research obtained the level of mastery of the current pedagogical competence of students and the type of learning style of each student that illustrated the characteristics of their learning style. Then, the model used in the development of learning planning was the learning model of learning that can learn students according to the learning style of students so as creating the activeness of students in learning, critical thinking, creative, communicative and collaborative.